Guideline for the Initial Management of Small Cell Lung Cancer (Limited and Extensive Stage) and the Role of Thoracic Radiotherapy and First-line Chemotherapy. Issue 10 (October 2018) - Sun, A.; Durocher-Allen, L.D.; Ellis, P.M.; Ung, Y.C.; Goffin, J.R.; Ramchandar, K.; Darling, G.
Abstract: Aims: We investigated the efficacy of adding radiotherapy to chemotherapy in patients with extensive stage small cell lung cancer (ES-SCLC) and the appropriate timing, dose and schedule of treatment for patients with ES-SCLC or limited stage SCLC (LS-SCLC). Materials and methods: The guideline was developed by Cancer Care Ontario's Program in Evidence-Based Care and by the Lung Cancer Disease Site Group through a systematic review of randomised controlled trials. Key recommendations: In patients with LS-SCLC (stage I, II and III), the addition of thoracic radiotherapy to standard chemotherapy is recommended. However, there is no clear evidence to inform definitive recommendations for optimal timing, sequential versus concurrent therapies and optimal dose or regimen. In patients with LS-SCLC, etoposide–cisplatin is the preferred regimen for adults who are being treated with combined modality therapy with curative intent. In patients with ES-SCLC (stage IV), there is insufficient evidence to recommend the addition of thoracic radiotherapy to standard chemotherapy as a standard practice for survival benefit; however, it could be considered on a case-by-case basis to reduce local recurrence. In patients with ES-SCLC, a platinum agent plus etoposide is the preferred regimen for adult patients who are being treated with combined modality therapy. Cisplatin and irinotecan represents an alternative treatment option to this, but is associated with increased rates of adverse events such as diarrhoea. Highlights: For LS-SCLC, the addition of radiotherapy to chemotherapy is recommended. For LS-SCLC, etoposide-cisplatin is the preferred regimen. For ES-SCLC, platinum-etoposide (preferred) or cisplatin-irinotecan is recommended.